2022
DOI: 10.1088/1572-9494/ac5245
|View full text |Cite
|
Sign up to set email alerts
|

Precision measurements and tau neutrino physics in a future accelerator neutrino experiment

Abstract: We investigate prospects of building a future accelerator-based neutrino oscillation experiment in China, including site selection, beam optimization and tau neutrino physics aspects. CP violation, non-unitary mixing and non-standard neutrino interactions are discussed. We simulate neutrino beam setups based on muon and beta decay techniques and compare Chinese laboratory sites by their expected sensitivities. A case study on Super Proton-Proton Collider and China JinPing Laboratory is also presented. It is sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Upcoming experiments addressing the above challenges are SBND (liquid argon) [125], MOMENT (water Cherenkov) [131], PROMPT (iron) [132], SHiP (tungsten) [133], DsTau (tungsten) [134], Hyper-Kamiokande (water Cherenkov) [88], and DUNE (liquid argon) [89].…”
Section: Reactor Neutrino Experimentmentioning
confidence: 99%
“…Upcoming experiments addressing the above challenges are SBND (liquid argon) [125], MOMENT (water Cherenkov) [131], PROMPT (iron) [132], SHiP (tungsten) [133], DsTau (tungsten) [134], Hyper-Kamiokande (water Cherenkov) [88], and DUNE (liquid argon) [89].…”
Section: Reactor Neutrino Experimentmentioning
confidence: 99%
“…As for the muon collider design, we take positron on target method (LEMMA) as an example, which has been proposed for high quality muon beam production [9,10] (Earlier studies using proton on target muon beams can be found in Refs. [11][12][13] ) Although it is still quite challenging to achieve enough high luminosity for muon beam collisions [6,7], we find it quite promising for neutrino oscillation studies, with comparable or even larger neutrino flux than other long baseline neutrino experiments, with more details to be discussed below. In the LEMMA approach, the incident positron energy is around 45 GeV, producing collimated muon pairs with opening angles of around 0.005 rad.…”
mentioning
confidence: 91%
“…Currently, the radon measurement methods worldwide mainly include the ionization chamber, electrostatic adsorption, and liquid scintillator measurement methods. Among them, due to the advantages of a high solubility coefficient and a low background, the liquid scintillator measurement method is widely used in dark matter and neutrino experiments, such as Jiangmen Underground Neutrino Observatory (JUNO) [5,6] and China Jinping Underground Laboratory (CJPL) [7,8]. Moreover, they all require high sensitivity for low-background detectors for radon measurements.…”
Section: Introductionmentioning
confidence: 99%